House-Hold Safety Recommendations for COVID-19 Pandemic - Akash, Amar; Bin Yar, Usama (Europasian Journal of Medical Sciences, 2020)
Since COVID-19 has erupted as a pandemic worldwide, according to the World Health Organization (WHO), about 4,758,937 cases are confirmed and approximately 316,300 deaths are claimed. Therefore, every individual is confining himself in quarantine at home. As people are staying at home for about 3 months, household precautions are important and should be followed to mitigate the proliferation of disease. Today, social distancing has become a national rule all over the world, so being eschewed is loving yourself. As the world is hit by a drastic pandemic, which has changed the entire pattern of living and everyone is in a tough situation. To help the community, it is necessary to have some guidelines and recommendations to opt regarding household functioning. Meanwhile, it is important to provide awareness and explicit misconceptions about coronavirus and COVID-19, also clarify its symptoms, its ways of transmission, and its preventions. Moreover, to suggest household recommendations for COVID-19, including healthcare practices, hygiene parameters, and transmission obstruction. Along with health-care suggestions for old-age persons, children, and most importantly for exposed individuals. Above all these usual discussed points, choice of food is the prime need to live alive, when you are quarantining yourselves. Thus, choosing certain types of food are suggested to be added to your daily diet, to stay healthy. Hence, practical implementation of all these recommendations is a core part of minimizing the spread of disease and remaining safe and healthy.